Hepatorenal protective effect of Antistax(®) against chemically-induced toxicity - Ahmed, Atallah F.; Al‑Yousef, Hanan M.; Al‑Qahtani, Jawaher H.; Al‑Said, Mansour S.; Ashour, Abdelkader Elbadawy Abbas; Al‑Sohaibani, Mohammed; , Syed Rafatullah (Wolters Kluwer - Medknow Publications and Media Pvt. Ltd, 2015)
BACKGROUND: Antioxidant natural products and chemoprevention are considered nowadays as an effective approach against health various disorders and diseases induced by oxidative stress or free radicals.